PENGARUH MEDIA PROYEKSI TERHADAP PENGETAHUAN SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM ( Eksperimen di SMP Nusantara Islamic School Setu Bekasi Timur ) - Alfi Fazriah; Acep Mulyadi (Turats, 2020)
Projection is intended to give material more real and interact more widely. By increasing students’understanding and interest in learning, it will accelerate the absorption of material by students andhave an influence on increasing knowledge of Islamic Religious Education. The author formulates 1problem how the influence of Projection Media on students’ knowledge of Islamic Religious EducationSubjects at SMP Nusantara Islamic School Setu-Bekais Timur for 2 months. This research is a typeof field ( field research ) by directly examining the place that is the object of research . The methodused in this research is the experimental method, while the approach in this research is a quantitativeapproach. The variable consists of two variables. Independent Variable (Projection Media) DependentVariable (Knowledge) of Students in Islamic Education Subjects). The sample in this study was usingpurposive sampling technique. Where the researcher deliberately determines the sample membersbased on references or suggestions from the teacher concerned. The samples taken in this study wereclass VIII B (30 students) as the experimental class, and class VIII A (30 students) as the control class.Projection media is quite influential on students’ knowledge of Islamic Religious Education subjects atSMP Nusantara Islamic School Setu, East Bekasi. This can be seen from the results of the Knowledgevalue that the Experiment class in the post-test section has an average of 78.93 while the KnowledgeControl class in the post-test section has an average of 78.77. The value of t count for the ProjectedMedia variable with a value of 11.762 > t table = 1.671. These results can be concluded that the datahave an effect.